A review of the importance of immune responses in luminal B breast cancer. (4th March 2017) - Nelson, Delia J.; Clark, Briony; Munyard, Kylie; Williams, Vincent; Groth, David; Gill, Jespal; Preston, Henry; Chan, Arlene
ABSTRACT: Historically, the immune environment was not considered an important target for breast cancer treatment. However, the association of lymphocytic infiltrates in triple negative and HER-2 over-amplified breast cancer subtypes with better outcomes, has provoked interest in evaluating the role of the immune system in the luminal B subtype that accounts for 39% of breast cancers and has a poor patient prognosis. It is unknown which immunosuppressive cell types or molecules (e.g., checkpoint molecules) are relevant, or where measurement is most informative. We hypothesize that a profound immunosuppressive tumor and/or lymph node milieu is prognostic and impacts on responses to therapies.